Pengembangan Perangkat Pembelajaran Fisika Berbasis Pendekatan Konflik Kognitif Untuk Meningkatkan Kemampuan Argumentasi Ilmiah Peserta Didik - Baiq Mia Rexa Liani; Syahrial Ayub; Wahyudi; Muh. Makhrus (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2021)
The purpose of this study was to determine the feasibility of physics learning tools based on cognitive conflict approach to improve students' scientific argumentation skills. The type of research used is Research and Development (R&D) with a 3D-based development model design consisting of 3 stages starting from Define, Design, and Develop. The product developed in this study is a learning device consisting of a syllabus, Learning Implementation Plan (RPP), Student Worksheets (LKPD), and test instruments. The feasibility of the learning device was obtained from the assessment of the validation questionnaire by the validator of physics lecturers and physics teachers. The assessment of the validation questionnaire produces qualitative and quantitative data. Qualitative data produces suggestions and inputs that are used as references to improve the learning tools developed. While the quantitative data is processed to get the value of validity and reliability. The quantitative data from the validation by the lecturers shows that the syllabus, lesson plans, and LKPD are in the very valid category and the test instrument shows a valid category. Meanwhile, the results of teacher validation showed that all the learning tools developed were in the very valid category. Data processing for reliability using the method Borich, known as the Percentage Agreement (PA). Reliability value of all learning tools, whether validated by lecturers or teachers, shows a reliable category because they have a value of more than 75%.